Aplikasi Konversi Data Buku dari Excel ke Database MySQL Berbasis Web pada Percetakan Braille Yayasan Raudlatul Makfufin - Dara Nabilah; Farizi Ilham; Abyaz Lutfi Wibowo; Andhika Julianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Raudlatul Makfufin Braille Printing Foundation (YARFIN) is a social institution producing Braille books for the visually impaired with a production capacity of 150 books per day. The production process requires book catalogue data in database format before being sent to the printing machine. However, data is still stored manually in separate Microsoft Excel files, making the transfer to the database a time-consuming manual process. This condition hinders the targeted increase in production capacity. This study develops a web-based application using PHP, MySQL, and the PhpSpreadsheet library to automatically convert book data from Excel to MySQL through validation, duplicate cleaning, and column mapping processes. Development uses the waterfall method with data collected through observation and interviews. Black-box testing on 10 scenarios shows a 100% success rate across all features. This system is expected to accelerate production datapreparation and support the improvement of YARFIN's printing capacity.